Penerapan Model ARCS (Attention, Relevance, Confidance, Satisfaction) Pada Mata Pelajaran PAI Untuk Meningkatkan Motivasi Belajar Siswa Kelas XI 7 Di SMAN 1 Palangka Raya - Raida, Raida; Malisi, M. Ali Sibram; Aghnaita, Aghnaita (Kamaya: Jurnal Ilmu Agama, 2025)
The learning model in Islamic Religious Education for class XI 7 at SMAN 1 Palangka Raya is less effective due to the boring lecture method, resulting in low student participation and learning outcomes. This research aims to determine the motivation for learning Islamic Religious Education (PAI) and analyze the application of the ARCS model (Attention, Relevance, Confidence, Satisfaction) in PAI learning at SMAN 1 Palangka Raya through the Classroom Action Research (CAR) method, which is conducted in two cycles that include the stages of planning, implementation, observation, and reflection. The subjects in this study were 31 students from class XI 7 at SMA Negeri 1 Palangka Raya, consisting of 11 male students and 20 female students. The research results show that the ARCS model effectively increases students' motivation and academic achievement. Teacher activity increased from 80% in cycle I to 93% in cycle II, while student activity rose from 76% to 93%. Learning motivation also increased on all indicators, such as enjoyment, interest, activity, and enthusiasm for learning. In conclusion, the ARCS model is effective in enhancing student motivation and engagement in PAI learning. Meanwhile, the distribution of the questionnaire on the aspects of enjoyment and interest increased from an average of 89% to 90%, interest and attention increased from an average of 80% to 86%, and activity and motivation to achieve increased from an average of 78% to 85%. The enthusiasm for learning increased from an average of 67% to 88%, and the desire to understand rose from 57% to 83%.